If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 55 = 3x + 23 Reorder the terms: 55 + 7x = 3x + 23 Reorder the terms: 55 + 7x = 23 + 3x Solving 55 + 7x = 23 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 55 + 7x + -3x = 23 + 3x + -3x Combine like terms: 7x + -3x = 4x 55 + 4x = 23 + 3x + -3x Combine like terms: 3x + -3x = 0 55 + 4x = 23 + 0 55 + 4x = 23 Add '-55' to each side of the equation. 55 + -55 + 4x = 23 + -55 Combine like terms: 55 + -55 = 0 0 + 4x = 23 + -55 4x = 23 + -55 Combine like terms: 23 + -55 = -32 4x = -32 Divide each side by '4'. x = -8 Simplifying x = -8
| 9(m+1)=54 | | 3(s+22)+10=88 | | -12/r=-3 | | -c^2+c+30=0 | | -3(s+18)=-15 | | 6x+40=2x+4 | | 6(k-74)-5=83 | | 6=4-w | | x+17=5x+5 | | 6=-3(d-9) | | 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 | | x^3+x^2+x-20=0 | | 5x-12=-2+5 | | Y+1(33)-28=21 | | 10n+50=5n-25 | | 3y^2+2x-1=0 |